Membangun Masyarakat Berwirausaha: UMKM, Fintech, dan Risikonya - Nenny A; Arko P; Saut P; Ktut Silvanita Mangani (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2023)
To support community service activity, a collaboration has been carried out with the Regional Government of the Mentawai Islands Regency and the Ugla Mentawai Simariuriu Foundation. This community service activity aims to build the community's economy in the Mentawai Islands Regency. The activity is carried out in the form of a Web Seminar (Webinar). The activity involved lecturers from various disciplines, as well as the UMKM National Secretariat, the Koperindag Office and the Mentawai Islands District Government. Activities are carried out in the form of seminars/webinar with the theme "Building Entrepreneurial Mentawai Communities." In accordance with the formulation of the problem that MSMEs need to anticipate with digital progress, especially Fintech developments, one of the materials that will be delivered to support this theme is "MSMEs, Financial Technology (Fintech) and Its Risks." This material is deemed necessary to be related to the development of the digital world that MSME actors need to know, especially in the Mentawai Islands area.